I have been struggling over this factoring problem literally all day. It makes absolutely no sense to me. I break it down into (x )(x ) so now I have to factor -5 right? however -5 is a prime number and 5 and 1, regardless of where the negative is placed, doesn't seem to add up to 9. Please don't answer this with rows of variables. explain in detail.
`2x^2+9x-5 = 0`
`2x^2+10x-x-5 = 0`
`2x(x+5)-1(x+5) = 0`
`(x+5)(2x-1) = 0`
x = -5 or x = 1/2
`x^2+bx+c = 0`
When you factoring this kind of function you need to adjust 'b' such a way that b = p+q where pq = c
In this case your question is not like this. it is `2x^2+9x-5 = 0`
To do this you need 1 in front of `x^2` instead of 2. So you can divide the equation by 2 as the first step. This is one method of solving that. There is the point you have failed.
`ax^2+bx+c = 0`
When you factoring this kind of function you need to adjust 'b' such a way that b = p+q where pq = ac
In this case your question is like this. it is 2x^2+9x-5 = 0
So when you are factoring you must find the factors that add up -5*2 = -10 NOT 5.
This numbers are 10 and-1 which gives addition as 9 and product as -10.
Hope you have understand the issue.